STUDY ANALYSIS OF LIGHTINING ARRESTER INSTALLATION LOCATION AT SUBSTATIONS - Zikri Asy'ari Ritonga; Adi Sastra P Tarigan; Solly Aryza (Sean Institute, 2022)
In general, a substation is an electrical system that functions to convert electrical energy to be distributed to consumers in general where electricity centers are connected to air transmission lines, and air transmission lines are susceptible to interference from outside the system, one of which is a lightning strike. Where in the operation of a substation there are several important equipment, one of which is a transformer, so a protection system must be installed on the transformer to minimize interference. Lightning strikes are dangerous for the components contained in the power center. The protection system is used to protect the power system and the equipment itself from lightning surges and short circuits. To maintain reliability and ensure normal operation, specifications for arresters installed on the HV side of the Tragi Binjai substation power transformer unit with a nominal voltage of 150 kV, have been in accordance with system requirements. The maximum distance between arresters and power transformers is 28.5 meters. The distance in the field is 3 meters, the voltage that arrives at the power transformer is 480 kV and is still below the value of the transformer's basic isolation level, so that the protection of the power transformer against lightning surges is very good